Optional opacity: A syntactically-based analysis of early Hebrew verb morphology. Issue 6 (December 2015) - Lustigman, Lyle
The study aims to account for the distribution of finite versus non-finite verbs during a developmental period when children use both types of verb forms in contexts requiring finiteness. To meet this goal, longitudinal samples from three Hebrew-acquiring children (aged 1;4–2;6) are examined from the onset of verb production and across the 'optional' period in which finite and non-finite verbs occur side by side. Each verb-containing utterance is specified for structural transparency (whether the verb has a clearly unambiguous target) and for additional clausal constituents. Analysis reveals that during the 'optional' period non-transparent verb forms favor elaborated syntactic environments (i.e., accompanied by objects and/or adverbs) at significantly higher rates than their transparent counterparts. These morpho-syntactic patterns in children's verb usage provide a line of explanation for the distribution of inflected versus non-inflected forms, and highlight the role of between-domain inter-relations in language acquisition.